In Vitro Inhibition of Fungal Antagonists on Fusarium sp., the Disease Causative Agent on Dragon Fruit Plant (Hylocereus undatus (Haw.) Britton & Rose) - Andriastini, Dewa Ayu; Ramona, Yan; Proborini, Meitini Wahyuni (Metamorfosa: Journal of Biological Sciences, 2018)
A research on in vitro inhibition of fungal antagonists, isolated from dragon fruit plantation in Sembung village, Bali, on Fusarium sp. (the disease causative agent of dragon fruit plant) was conducted with the main objective to investigate the effectiveness of these fungal antagonists to inhibit the in vitro growth of the pathogen. Dual assay method was applied in this experiment. The results showed that three potential fungal antagonists were successfully isolated in this research and they were identified as Trichoderma harzianum, Aspergillus niger , dan Paecilomyces lilacinus. All these fungal antagonists showed antagonistic activity against Fusarium sp. which was statistically significant (p<0.05) when compared to control. This indicated that all antagonist isolates were potential to be developed as biocontrol agent candidates.